An integrated microfluidic system for hepatotoxicity assessment based on gene expression profiling : from tissue homogenization to RT-PCR - Zhang, Lei (2017)
A practical, rapid, low-cost, and largely ‘equipment-free’ point-of-care (POC) testing device for hepatotoxicity assessment is, at this juncture, unavailable/unreported. In this thesis, we will describe our effort towards the design and realization of this POC device – two lab-on-a-chip (LOC) systems for gene of interest (GOI) expression detection with crude liver tissue input for hepatotoxicity assessment. For the first LOC system, we describe our semi-integrated 2-chip (a tissue homogenization/mRNA extraction chip and a stationary multiplex microfluidic reverse transcription-polymerase chain reaction (RT-PCR) chip) LOC system with real-time fluorescent detection. We demonstrate that our tissue homogenization/mRNA extraction chip (based on our verified modification of a selected conventional manual tissue homogenization and mRNA extraction method (for smaller sample input and less chemical reagents)) has an mRNA extraction efficiency comparable to our said modification of selected conventional manual protocol. With liver tissue samples from our pre-clinical drug toxicity study on mice administrated with different dosages of cyclophosphamide, we demonstrate that our tissue homogenization/mRNA extraction chip is applicable for semi-quantitative multiplex gene expression studies. Specifically, the gene expression level of GOIs (AST, AST1, and ALT1) derived from our tissue homogenization/mRNA extraction chip elevates with increasing dosages of cyclophosphamide and is consistent with that obtained from the conventional laboratory procedures in reported studies. We perform multiplex RT-PCR for GOIs (AST and ALT) on our stationary multiplex RT-PCR chip with the mRNA extracted from our tissue homogenization/mRNA extraction chip. The electrophoresis gel image and real-time fluorescent images of our on-chip multiplex RT-PCR process indicate elevations of expression level of both GOIs (AST and ALT) with increasing dosages of cyclophosphamide. These results are consistent with that obtained from the conventional laboratory procedure. For the second LOC system, we describe a fully-integrated LOC system comprising a tissue homogenization/mRNA extraction component and a continuous-flow RT-PCR component for rapid processing within an enclosed microfluidic environment. We demonstrate that our continuous-flow RT-PCR chip is able to amplify a specific gene (ALT1) rather rapidly – within 45 minutes, which is equivalent to 50% time reduction of the conventional RT-PCR process. Nevertheless, our on-chip RT-PCR only achieves 60% amplification efficiency of the conventional RT-PCR. By integrating a tissue homogenization/mRNA extraction chip and a continuous-flow RT-PCR chip, we realize a fully-integrated microfluidic system. This system features rapid processing – 33% time reduction of our first LOC system. However, our integrated LOC system only achieves ~50% amplification efficiency of the conventional manual procedure. In short, our work herein contributes towards the continuing development of a new generation of a practical, rapid, low cost POC testing device with “sample-in-answer-out” capability for hepatotoxicity assessment as part of liver disease diagnosis.